Evaluating the impacts of the covid-19 pandemic on risk perception in the hospitality industry in Malaysia - Wong, Jun Hou (2024)
Aims to brief the challenges faced by the Malaysian hospitality industry and explore the evolving landscape of risk perception among its employees in the wake of the pandemic. The urgency of comprehending how the pandemic shapes risk perception within the Malaysian hospitality industry by emphasizing the need to explore employee attitudes, social dynamics, stress-induced impacts, and hygiene behaviours. Moreover, this chapter will cover on the research background, problem statement, research objective, research question and follow by significance of study.